2019
DOI: 10.1029/2018jd029946
|View full text |Cite
|
Sign up to set email alerts
|

A Modeling Study of the Effects of Vertical Wind Shear on the Raindrop Size Distribution in Typhoon Nida (2016)

Abstract: In this study, the effects of vertical wind shear (VWS) on the raindrop size distribution in tropical cyclone are investigated, based on the theoretical analyses that intense VWS, which commonly appears in the lower layers of tropical cyclones, can enhance the collisional breakup of raindrops. This is achieved by comparing the numerical sensitivity experiments of Typhoon Nida (2016) using Weather Research and Forecasting model against the polarimetric radar and disdrometer observations. In the control run with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Based on the reduction of simulated STD( D m ), we suppose limited DSD variability in the schemes is highly likely to be caused by unrealistic constrictions related to warm‐rain processes. Previous studies have revealed that the self‐collection (breakup) processes are commonly parameterized by simplified empirical formulas in microphysics schemes, and the key parameters of which have a critical impact on the values of DSD parameters (Deng et al., 2019; Morrison et al., 2012; Planche et al., 2019; Saleeby et al., 2022). Take THOM for example, the self‐collection (breakup) formula is presented as: normaldNrcol=2EcNrW, $\mathrm{d}{N}_{rcol}=2{E}_{c}{N}_{r}W,$ where d N rcol denotes the raindrop number concentration tendency via self‐collection (breakup), N r denotes the existing raindrop number concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the reduction of simulated STD( D m ), we suppose limited DSD variability in the schemes is highly likely to be caused by unrealistic constrictions related to warm‐rain processes. Previous studies have revealed that the self‐collection (breakup) processes are commonly parameterized by simplified empirical formulas in microphysics schemes, and the key parameters of which have a critical impact on the values of DSD parameters (Deng et al., 2019; Morrison et al., 2012; Planche et al., 2019; Saleeby et al., 2022). Take THOM for example, the self‐collection (breakup) formula is presented as: normaldNrcol=2EcNrW, $\mathrm{d}{N}_{rcol}=2{E}_{c}{N}_{r}W,$ where d N rcol denotes the raindrop number concentration tendency via self‐collection (breakup), N r denotes the existing raindrop number concentration.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that SST played a primary role in pCO 2sea during the initial limited time period of Typhoon Merbok. Furthermore, there was no significant slowdown in the temperature-induced pCO 2sea relative to non-temperature factors during the second step of Typhoon Nida (figure 8), indicating that SST may not only be affected by deeper water but may also be influenced by other factors such as heavy rainfall, which could cause a decrease in SST (Deng et al 2019, Feng et al 2021.…”
Section: Temporal Changes In Pco 2sea and Co 2 Fluxes In In Northern ...mentioning
confidence: 94%
“…With the development of cloud and precipitation observations, polarimetric radar has gradually been used to validate the model in simulating the raindrop characteristics within the TC system [32][33][34]. The horizontal reflectivity factor (Z H , unit: dBZ) is a variable that represents both particle size and number concentration in the detective volume, while the differential reflectivity (Z DR , unit: dB) only expresses the size information of particles.…”
Section: Introductionmentioning
confidence: 99%